Can standardised clinical examination of athletes with acute groin injuries predict the presence and location of MRI findings?. Issue 24 (16th August 2016) - Serner, Andreas; Weir, Adam; Tol, Johannes L; Thorborg, Kristian; Roemer, Frank; Guermazi, Ali; Hölmich, Per
Abstract : Background: Little is known about the value of clinical examination in relation to diagnostic imaging for acute groin injuries in athletes. Primary aim: to investigate whether clinical examination tests predict a positive or negative MRI result (MRI±). Secondary aim: to assess accuracy of clinical tests to localise injury in MRI+ cases. Methods: We consecutively included 81 male athletes with acute groin injuries. Standardised clinical examination (palpation, resistance and stretch tests) and MRI were performed within 7 days of injury. Diagnostic statistics including positive and negative predictive values (PPV/NPV) were calculated. Results: 85 acute injuries were found on MRI in 64 (79%) athletes with 17 (21%) athletes having MRI− injuries. Palpation had the highest NPV (91–96%, (95% CI 69% to 99%)). 3 specific adductor examination tests (resisted outer range adduction, squeeze test with hip neutral and long lever, and passive adductor stretch) showed 80–81% (95% CI 63% to 91%) probability of an MRI+ adductor lesion when positive, all with high accuracy of a correct MRI location (PPV 93–97% (95% CI 76% to 100%)). Hip flexor tests showed poor ability to predict MRI+ lesions (PPV 34–63% (95% CI 20% to 84%)) and low accuracy (PPV 17–71% (95% CI 7% to 85%)). Conclusions: 21% of athletes had negative imaging and the absence of palpation pain was best at predicting an MRI− result. Specific adductor examination tests accurately predicted MRI+ adductor injuries. Hip flexor clinical tests were poor at predicating and localising MRI+ injuries in the hip flexors. Clinical examination appears sufficient to diagnose acute adductor injuries, whereas MRI could assist in accurately locating acute hip flexor injuries.